2021
DOI: 10.3390/jpm11111074
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Stretching in Post-Stroke Spasticity and Range of Motion: Systematic Review and Meta-Analysis

Abstract: Spasticity is one of the most frequent and disabling clinical manifestations of patients with stroke. In clinical practice, stretching is the most widely used physiotherapeutic intervention for this population. However, there is no solid evidence for its effectiveness. The aim of this study was to evaluate the effectiveness of different types of stretching in reducing post-stroke spasticity. Research was carried out until March 2021 in the following scientific databases: PubMed, CINAHL, Scopus, Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 58 publications
(161 reference statements)
0
13
0
1
Order By: Relevance
“…The CP programme focused on 1 h/day of overall functional recovery of the patient (including the upper limb), based on mixed techniques with different approaches [57][58][59][60]. Patients assigned to the CP group received 1 more hour of specific LE rehabilitation consisting of stretching [61,62], passive, assisted, and active exercises in many directions in The CP programme focused on 1 h/day of overall functional recovery of the patient (including the upper limb), based on mixed techniques with different approaches [57][58][59][60]. Patients assigned to the CP group received 1 more hour of specific LE rehabilitation consisting of stretching [61,62], passive, assisted, and active exercises in many directions in the lower extremity working space (e.g., hip joint flexion and extension, abduction and adduction, rotation internal and external, knee flexion, and extension).…”
Section: Interventionsmentioning
confidence: 99%
“…The CP programme focused on 1 h/day of overall functional recovery of the patient (including the upper limb), based on mixed techniques with different approaches [57][58][59][60]. Patients assigned to the CP group received 1 more hour of specific LE rehabilitation consisting of stretching [61,62], passive, assisted, and active exercises in many directions in The CP programme focused on 1 h/day of overall functional recovery of the patient (including the upper limb), based on mixed techniques with different approaches [57][58][59][60]. Patients assigned to the CP group received 1 more hour of specific LE rehabilitation consisting of stretching [61,62], passive, assisted, and active exercises in many directions in the lower extremity working space (e.g., hip joint flexion and extension, abduction and adduction, rotation internal and external, knee flexion, and extension).…”
Section: Interventionsmentioning
confidence: 99%
“…Stretching has been most widely used in the physical management of post-stroke spasticity [ 8 ]. However, no conclusive evidence was analyzed on the effectiveness of stretching for post-stroke spasticity [ 9 ]. This meta-analysis proposed an individual stretching method based on stroke patients’ characteristics [ 9 ].…”
mentioning
confidence: 99%
“…However, no conclusive evidence was analyzed on the effectiveness of stretching for post-stroke spasticity [ 9 ]. This meta-analysis proposed an individual stretching method based on stroke patients’ characteristics [ 9 ]. Zhang et al [ 10 ] reported that endovascular coil embolization for aneurysmal subarachnoid hemorrhage (SAH) showed a higher risk than surgical clipping.…”
mentioning
confidence: 99%
See 2 more Smart Citations